2008
DOI: 10.1016/j.bandc.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of intellectual ability with morphology of the hippocampus and amygdala in healthy adults

Abstract: Several prior imaging studies of healthy adults have correlated volumes of the hippocampus and amygdala with measures of general intelligence (IQ), with variable results. In this study, we assessed correlations between volumes of the hippocampus and amygdala and full-scale IQ scores (FSIQ) using a method of image analysis that permits detailed regional mapping of this correlation throughout the surface contour of these brain structures. We delineated the hippocampus and amygdala in high-resolution magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 79 publications
3
34
0
Order By: Relevance
“…It has been also described that cytoarchitectonic differences in primary visual cortex may underlie observed sex differences in the processing of visuospatial and motion information (Amunts et al, 2007). Amat et al (2008) found a significant inverse correlation between intellectual abilities and hippocampus volume which was independent of sex.…”
Section: Introductionmentioning
confidence: 78%
“…It has been also described that cytoarchitectonic differences in primary visual cortex may underlie observed sex differences in the processing of visuospatial and motion information (Amunts et al, 2007). Amat et al (2008) found a significant inverse correlation between intellectual abilities and hippocampus volume which was independent of sex.…”
Section: Introductionmentioning
confidence: 78%
“…However, a correlation between IQ and amygdala volume did not reveal any significant associations, consistent with previously reported findings in healthy adults. 62 Fourth, clinical outcome measures revealed that by 12 months many of the adolescents with bipolar disorder who began the study manic were euthymic (Table 1). Associations revealed a significant correlation between baseline YMRS scores and amygdala volume in the bipolar group; however no correlation was found between 12 month YMRS scores and amygdala volume.…”
Section: Discussionmentioning
confidence: 99%
“…One research group has reported that higher IQ is associated with higher levels of NAA and lower levels of Cho in parietal-occipital white matter (Jung et al, 1999; Jung, Yeo, Chiulli, Sibbitt, & Brooks, 2000). A different study investigated the relationship between amygdala volume and intellectual ability and reported negative findings (Amat et al, 2008). Based on these reports, we suggest that the relationship between NAA and IQ in the controls most likely reflects general neural functioning rather than individual differences within cellular properties of the amygdala specifically.…”
Section: Discussionmentioning
confidence: 99%